Research with high-risk populations : balancing science, ethics, and law - Buchanan, David Ross; Fisher, Celia B.; Gable, Lance (American Psychological Association, 2009)
"This book provides in-depth analyses and guidance to social scientists regarding ethical and legal responsibilities that may arise in the course of conducting research with high-risk populations and in responding appropriately to threats of suicide, child abuse, and violence that may arise during the course of data collection. These discussions offer valuable lessons both for researchers who are planning to investigate the etiology of these particular problems and for researchers who may be confronted with similar threats of harm while investigating other health concerns such as HIV/AIDS or substance abuse. Because of the paucity of informed analyses of this critical topic area, researchers now find themselves caught between contradictory assumptions about the nature of the risks involved in descriptive research with populations at risk of violence and other harms. On the one hand, the traditional view has been that descriptive research poses minimal risk, as it is completely unlike medical experiments in which participants are exposed to novel experimental treatments. One common view is that if the research involves merely asking people questions, then the ethical risk of such research is limited to the harms that could emerge if confidential information were to be inadvertently disclosed. On the other hand, research with high-risk populations raises acute and appropriate questions for investigators, institutional review boards (IRBs), and other interested parties about a duty to protect: When or at what point does the threat of harm, such as suicide, child abuse, or violence, warrant overriding confidentiality protections?"--Introduction. (PsycINFO Database Record (c) 2009 APA, all rights reserved)